(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2012)
In the article the sources of enrichment of the vocabulary are exposed in the Ukrainian official and business style in the 20–30th years of the 20th century . The author reasons, that in the researched period dialectal vocabulary, archaisms and neologisms are included to lexical composition.